Multidrug Resistant Enteric Bacteria from Cancer Patients Admitted in Douala Laquintinie Hospital, Littoral Region of Cameroon - Michael F. Kengne; Ornella D. Tsobeng; Ballue S. T. Dadjo; Victor Kuete; Armelle T. Mbaveng (Canadian Journal of Infectious Diseases and Medical Microbiology)
Patients with cancer have weakened immune systems, making them more vulnerable to infections. This study was carried out to determine the bacterial origins of enteric disorders in cancer patients and noncancer patients at the Oncology Department of Laquintinie Hospital in Douala. A cross-sectional study was conducted from October 2021 to March 2023. Stool samples from 307 cancer patients with enteric disorders and 200 noncancer patients with enteric disorders were examined to diagnose the presence of bacteria using various techniques. Among all participants in this study, 62.13% were female and 37.87% were male. The average age of the participants was 46.38 ± 15.81 years, with a minimum age of 10 years and a maximum age of 84 years. The average age of participants was significantly higher (p<0.000) in cancer patients (49.54 ± 14.65 years) compared to noncancer patients (41.53 ± 16.33 years). Proteus mirabilis, Proteus vulgaris, Salmonella typhi, Enterobacter cloacae, Klebsiella pneumoniae, Yersinia intemedia, and Klebsiella oxytoca were more frequently isolated in cancer patients than in noncancer patients, with the respective percentages of 56.25% versus 43.75%, 50.00% versus 50.00%, 61.66% versus 38.34%, 66.66% versus 33.34%, 72.22% versus 27.78%, 80.00 versus 20.00%, and 100% versus 0.00%. Most isolates were sensitive to imipenem (IMP), gentamicin (GEN), and amikacin (AMK). Proteus vulgaris, the most prevalent isolate, showed significantly high resistance (with p<0.05) in cancer patients compared to noncancer patients at amoxicillin/clavuranic acid (AMC) (89.13% versus 41.30%), ceftriaxone (CTR) (63.04% versus 39.13%), ciprofloxacin (CIP) (65.22% versus 34.18%), and tetracycline (TET) (93.48% versus 63.04%). Multidrug resistance was observed in cancer patients compared to noncancer patients for Klebsiella pneumoniae (85.00% versus 60.00%), Salmonella typhi (84.62% versus 60.00%), and Klebsiella oxytoca (86.49% versus 43.48%). The increase in the number of Gram-negative infections among cancer patients, as shown in the present study, highlights the need for broad-spectrum therapy and effective planning of control programs to reduce bacterial diseases among cancer patients.